2018
DOI: 10.1097/sap.0000000000001571
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Lymph Nodes During Lymph Node Transplantation

Abstract: Quantifying lymph nodes in vascularized lymph node transfer (VLNT) has been performed using preoperative percutaneous ultrasound. The higher resolution and accuracy of intraoperative ultrasound (IOUS) over transcutaneous ultrasound has been demonstrated in the radiology literature for the identification and characterization of finer structures including hepatic lesions, pancreatic lesions, and biliary or pancreatic ducts. We hypothesize that IOUS during VLNT would be a superior method to quantify and map lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…9 That is, arterial inflow to the transferred tissue was significant enough to result in decreased peripheral flow to the extremity. A porcine study of the omental flow-through flap demonstrated that flow dynamics were unchanged at the distal arterial anastomosis 7 even when the omental flap was clamped. 10 Thus, in a flow-through configuration, the arterial inflow to the flap is significantly less than in an end-to-side configuration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 That is, arterial inflow to the transferred tissue was significant enough to result in decreased peripheral flow to the extremity. A porcine study of the omental flow-through flap demonstrated that flow dynamics were unchanged at the distal arterial anastomosis 7 even when the omental flap was clamped. 10 Thus, in a flow-through configuration, the arterial inflow to the flap is significantly less than in an end-to-side configuration.…”
Section: Discussionmentioning
confidence: 99%
“…used intraoperative ultrasound (IOUS) to identify and quantify lymph nodes as previously described. 7 The omentum was harvested and the proximal and distal gastroepiploic vessels were identified.…”
Section: Methodsmentioning
confidence: 99%
“…The time interval from lymphedema diagnosis to the initial surgical consultation appeared to be shorter in the fluid-dominant cohort with a median of 2 (1-4) years compared to the fat-dominant group at 8 (5-15) years. For lymphedema patients with fat-dominant disease, the median time from debulking to VLNT was 18 (16)(17)(18)(19)(20)(21) months. For all patients, the median flap weight was 23 (18-28) grams with a median of 6 (5-7) lymph nodes transferred, as identified on intraoperative ultrasound.…”
Section: Resultsmentioning
confidence: 99%
“…The number of lymph nodes within the flap and the overall flap weight were recorded. Our intraoperative duplex ultrasound process for lymph node identification and quantification during VLNT has previously been described in detail [ 22 , 23 ] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation